An Interleaved Battery Charger Circuit for a Switched Capacitor Inverter-Based Standalone Single-Phase Photovoltaic Energy Management System - Manesh Patel; Zhongfu Zhou (Energies, 2023)
A single-phase bidirectional DC/DC battery charger with a P&O MPPT current control strategy for a standalone energy management system has been integrated with an interleaved switched capacitor DC/AC inverter with an RMS feedback phase-shifted unipolar sinusoidal PWM control strategy. In the published literature, P&O MPPT control is used to drive a boost converter connected in parallel to a battery charger; this modified strategy combines a P&O MPPT algorithm with current control to drive an interleaving buck-boost battery charger. This battery charger circuit is connected in parallel to a closed loop controlled interleaved inverter that feeds the AC home load. MATLAB/Simulink based simulation circuit was developed and used to validate the successful integration of the interleaved battery charger with the global system. To do this, the system is tested with varying input conditions of irradiance and temperature. The system’s response to these variable inputs is monitored and analysed. The simulation results show the proposed method is effective for standalone battery-based PV systems. The system provides a more efficient and faster response compared with both an interleaved and non-interleaved voltage-controlled battery charger circuit that is also integrated with the global system. This battery charger control strategy is also shown to protect the battery from over-charging as well as discharging below 25%, which can improve and protect the long-term battery performance. Compared with novel industry approaches, the proposed system is simpler by nature due to the reduced number of conversions and therefore a reduced number of components which provides economic advantages.